Analysis of the Speed Increasing Drive based on Plane Steel Ball Mechanism and Its Influencing Factor - Feng Zhanzong; Wei Laisheng; Yin Yunbao; Fang Qiang; He Lipeng (Jixie chuandong)
The feasibility of taking the plane steel ball transmission mechanism as a speed increaser is analyzed. Through building the dynamics model of a meshing pair of the presented transmission mechanism,the self- locking mechanism of a meshing pair is analyzed. The research results show that each meshing pair is unavoidably self- locking in a certain area. However,the plane steel ball transmission mechanism could be used to realize the speed increasing transmission by the tooth profile of meshing pair is modified since the transmission has multi- meshing pairs and every meshing pair is on different phase.